2022
DOI: 10.1111/jfs.12972
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance of Escherichia coli in fish supply chain: A preliminary investigation

Abstract: Ninety‐five Escherichia coli isolates recovered from different supply points of freshwater fish namely fish pond (W1, n = 16), wholesale fish market (W2, n = 14), retail fish market (R1, n = 29), street fish vending unit (R2, n = 30), and modern fish vending unit (R3, n = 6) were investigated for antimicrobial‐resistant profile and prevalence of antibiotic‐resistant genes. Overall, multidrug‐resistant (MDR) E. coli in the fish supply chain was 21% with higher MDR incidence in the downstream fish supply points.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Additionally, the study identified the presence of sulfonamide resistance genes, sul 1 and sul 2. Another study, from India, also identified that 21% of fish Escherichia coli carried multidrug-resistant (MDR) genes, including the sulfonamide resistance gene sul 1 [38]. Therefore, the residues of sulfonamide antibiotics in aquatic products deserves more attention, and more extensive testing should be conducted to explore their residues and provide data to support the evaluation of the health risks from their consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study identified the presence of sulfonamide resistance genes, sul 1 and sul 2. Another study, from India, also identified that 21% of fish Escherichia coli carried multidrug-resistant (MDR) genes, including the sulfonamide resistance gene sul 1 [38]. Therefore, the residues of sulfonamide antibiotics in aquatic products deserves more attention, and more extensive testing should be conducted to explore their residues and provide data to support the evaluation of the health risks from their consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly isolated from fish intestines and found in contaminated water. E. coli has been seen invading other fish tissues such the gills, kidneys, muscles, and bladder (Kusunur et al 2022;Yohans et al 2022).…”
Section: E Colimentioning
confidence: 99%